Faktor-faktor yang mempengaruhi manajemen pajak pada perusahaan manufaktur - HENNY HENNY; MEIRISKA FEBRIANTI (Jurnal Bisnis dan Akuntansi, 2016)
The purpose of this study is to investigate the factors affecting tax management of listed manufacturing company. Those factors are firm size, leverage, profitability, fixed asset intensity and tax incentive to tax management using effective tax rate as a indicator.Data for this study comprises of the financial ratios calculated from the financial statement of the 48 manufacturing companies listed in Indonesia stock exchange over the three years period 2012-2014. Analysis tool used multiple linear regression with t test, F test and test the coefficient of determination.The research finding can be summarized as follows. First, profitability and tax incentive statistically significant to predict tax management (effective tax rate). Another result showed that firm size, leverage and fixed asset intensity did not significantly influence tax management (effective tax rate).